Sex differences in the association between Body Mass Index and cognitive function in Parkinson disease: a cross-sectional study - Wang, QiuShuang; Bian, Jing; Sun, Yi; Shi, YaoZhou; Zhao, ZiXuan; Zhao, HuaShuo (Frontiers in Nutrition, 2024)
Objective: This study utilized a binary logistic regression model to explore the relationship between Body Mass Index (BMI) and cognitive function in Parkinson's disease (PD) patients. Methods: In this cross-sectional study, data were obtained from 1005 Parkinson's patients enrolled in the Parkinson's Progression Markers Initiative (PPMI) from 2010 to 2023, including 378 females and 627 males. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) scale, and the correlation between BMI and cognitive function was determined using binary logistic regression.Results: The median age of enrollment was 63.6 (56.2, 69.6) years old, including 378 (37.6%) females and 627 (62.4%) males. In the final adjusted model, a significant positive correlation was found between BMI and the prevalence of cognitive impairment in females (OR=1.06, 95% CI=1.01~1.12, P=0.022), while no correlation was found in males (OR=1.03, 95% CI=0.99~1.08, P=0.165). The results after categorizing BMI indicate that, among females, the risk of cognitive impairment increases for both groups with BMI ≥ 30 kg/m 2 and those with 25 ≤ BMI < 30 kg/m 2 compared to the reference group with BMI < 25 kg/m 2 , with a P for trend <0.001 indicating a stable and strong association between BMI and cognitive impairment in females. In males, the results were not significant. The trend of linear fitting was consistent with the above results.In female Parkinson's patients, there is a positive correlation between BMI and cognitive impairment, while no correlation was found in male patients. This study provides new evidence of sex differences in the correlation between BMI and cognitive impairment among Parkinson's patients.The role of sex differences in the relationship between BMI and cognitive impairment should be considered in future research.